Et signalement af ledelsesdilemmaet: Identitet og mening til forhandling - Hertel, Frederik; Fast, Michael (Academic Quarter | Akademisk kvarter, 2013)
In this article the reader is offered a new understanding of management through an analysis on the phenomenon we define as the management dilemma. The concept describes the situation occurring when a manager considers creating an I-It relation to the employee as necesserary in order to achive the compagny aims. The challenge for the manager is that the objectification of the employee will create a managerialdistance to the employee and thereby a distance to the organization. The managerialdistance makes it impossible for the manager to achive understanding of the situation as it occur for the employee. During the following article a case is analyzed in order to create a deeper understanding of the management dilemma. The article focuses upon the contradictions in organizational and management thinking and interaction, in relation to I - It, I - Thou, self and reflection.